Parenting and human development: differences in understanding after participating in family intervention program - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Alwi, Azlin; Mohamed Iqbal, Mimi Iznita (Universiti Tun Hussein Onn Malaysia, 2015)
Parenting is one of the important elements that contribute optimum human development. There are number of ways parents can acquire parenting skills including through intervention program. Family intervention programs have been found to be one of the effective strategies for educating the public, particularly parents about parenting issues and skills. In relation to this, a study was conducted to examine how parents’ understanding changes after attending a family intervention program. It was hypothesized that the understanding of participants will increase after learning new techniques for effective parenting from the program. A total of 268 study participants from seven districts in peninsular Malaysia were enrolled, with average age between 41-50 years. All participants completed a questionnaire, which consisted of 30 questions regarding the program modules, both before and after the intervention program. Results of the split-plot ANOVA test demonstrate that though there is no significant interaction effect between location and pre-and post-scores, there is evidence of a small increase from before to after the completion of the program. Factors such as quality of program implementation, competencies of facilitators, and limitation of funds might account for the non-significant results. Implications and suggestions are discussed concerning the improvement and development of family-based interventions.